Pengaruh porting saluran intake dan exhaust terhadap kinerja kawasaki ninja 2 tak 150 cc - Hendro Hendro Prastyo; Tulus Supriyanto; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2023)
After COVID, activities for motor racing championship competitions have increased year after year. As a result, an engine change is necessary to compete in motor racing events because utilizing a factory standard engine will not produce the best results. It basically has to be modified on the machine because factory standard machines have standard speed and are not ideal for the event motor racing. The goal of this study was to determine how intake and exhaust channel porting affected the 150 cc Kawasaki Ninja's performance and how the results varied in these areas. The experimental procedure entailed reshaping the intake and exhaust holes in the cylinder block from the intake port, which measured 44 mm to 42.5 mm from the upper lip, and the exhaust, which measured 36 mm to 41.5 mm, and exhaust height, which measured 35 mm to 29.5 mm from the upper lip of the cylinder block, a Dynojet test kit on a 150 cc Kawasaki Ninja 2 stroke motorcycle was used to determine the horsepower and torque data obtained. The results of the standard cylinder block data after porting adjustments to the intake and exhaust holes show that the torque results on the standard cylinder block get data from 19.31 at 6,723 rpm to 21.85 at 8,018 rpm, and the HP results on the standard block get data from 23.49 HP at 6,915 rpm to 27.92 HP at 8,584 rpm. The results of this investigation suggest that power and torque can be increased by changing the intake and exhaust ports. Engine performance will be impacted by increased power and torque. The process of adding ports to the intake and exhaust is only getting started with this research. Therefore, more study is required. In order to achieve the best power and torque outputs for the demands of motor racing, research can be conducted by creating porting adjustments